Hubungan Strategi Campuran Pemasaran dalam Perusahaan Kecil dan Sederhana (PKS) dengan Kepuasan Pengguna: Sektor Perkilangan (Produk Makanan dan Minuman) - Ida Nadia, Hamidon (2009)
This study is carried out to investigate the relationship between marketing mix strategy of small medium enterprise (SME) business and consumer satisfaction. The study is focusing on food and beverages products. The outcomes of this research are essential to readers in order to understand the dimension that influences consumer to buy the products. Furthermore, the research is important to recognize the relationship of the marketing mix strategy which consist of Product, Price, Promotion and Place towards consumer satisfaction. Quantitative method had been used in this study. The respondents come from 172 of studenst in Universiti Utara Malaysia (UUM). The result shows there are significant relationship between product, price, promotion and place towards consumer satisfaction. Further research reveals there is significant relationship between marketing mix strategy and consumer satisfaction. Marketing mix strategy represents 37% variance of consumer satisfaction. The satisfaction influenced by dimension of product, promotion and place.